1865-66 N.C. Sess. Laws 22, Priv. Laws, ch. 7, § 64. - (:unkn) unknown (General Publisher, 1866)
That they may prohibit and prevent, by penalties, . . . and also the firing of guns, pistols, crackers, gun-powder or other explosive, combustible or dangerous materials in the streets, public grounds, or elsewhere within the city."
--
Keywords: DISCHARGE